GeoFun App: The Interactive Android-Based Learning Media in Curved Surface Geometry Learning - Halqi, Muhammad; Istiqomah, Sucita Annisa Belia; Supiyati, Sri; Isnawan, Muhamad Galang; Alsulami, Naif Mastoor (FKIP Universitas Lampung, 2025)
This study aims to develop Android-based learning media on the topic of curved surface geometry, named GeoFun App. The research method was a development research using the ADDIE model design. Participants in this study were ninth-grade students and mathematics teachers at one of the Islamic Junior High Schools (Madrasah Tsanawiyah) in East Lombok Regency, Indonesia, as well as two experts. The instruments used were media and material validation sheets, teacher and student response questionnaires, and learning outcome tests. Application validity analysis was conducted using Aiken’s V scale and the Likert scale. Absolute evaluation was used to test practicality, while the N-Gain method was applied to assess effectiveness. The research findings showed that the GeoFun App media met the validity criteria, with a validity score of 0.869 (material experts) and 0.844 (media experts), categorized as very valid. It achieved a practicality score of 60% from teachers (practical category) and 94.48% from students (very practical category). The result demonstrated an N-Gain of 76.3% and was categorized as effective. The GeoFun App possessed several unique superior characteristics, such as engaging assessments (quizzes, tests, and games), facilitating online and face-to-face learning, and integrating religious aspects (the use of Shalawat Nahdlatin and prayers on the initial display, as well as learning etiquette). Therefore, this study concluded that the GeoFun App met the criteria of validity, practicality, and effectiveness, as it was tailored to student needs and learning difficulties and was Android-based, making it familiar to students. The GeoFun App thus provides an alternative that teachers can use to optimize students’ mathematical competence in learning curved surface geometry. This study recommends that future research continue to enhance the application's compatibility so that it can be used on lower Android versions. Keywords: ADDIE model, curved surface geometry, GeoFun App.